DOI: 10.31274/rtd-180813-13411
|View full text |Cite
|
Sign up to set email alerts
|

Legume establishment and persistence at sites varying in landscape position, grazing method, and soil characteristics

Abstract: Iowa pastures are diverse in the landscapes and soil conditions present within small area units. Introducing legumes into these areas has the potential to improve seasonal distribution and quality of the pasture forage. This study was performed to quantify the spatial and temporal variation in legume contribution to the plant community when seeded into established cool-season grass pastures. Pastures were seeded with a mixture of eleven legumes and then divided into three grazing methods (non-grazed, continuou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 142 publications
(260 reference statements)
0
2
0
Order By: Relevance
“…Development of farm‐specific BMPs is hampered by the wide variation among farms in landscape features, nutrient status, crop and animal types and numbers, and farm management styles. Pasture species composition can affect nutrient removal and optimal pasture production (Harmoney et al, 1998; King et al, 2015). For example, bermudagrass [ Cynodon dactylon (L.) Pers.]…”
mentioning
confidence: 99%
“…Development of farm‐specific BMPs is hampered by the wide variation among farms in landscape features, nutrient status, crop and animal types and numbers, and farm management styles. Pasture species composition can affect nutrient removal and optimal pasture production (Harmoney et al, 1998; King et al, 2015). For example, bermudagrass [ Cynodon dactylon (L.) Pers.]…”
mentioning
confidence: 99%
“…Although not tested in this experiment, the lowest absolute and relative abundance of legume species in the grazing treatment may have been correlated with selective grazing of legumes by cattle. Numerous studies have demonstrated cattle's preferential grazing of legumes (Harmoney et al, 1998) and palatable native forbs and legumes (Berg, 1990;Hickman and Hartnett, 2002), although the effect of grazing varied by grazing intensity. Berg ( 1990) found that grazing was negligible on purple prairie clover populations but significantly lowered Illinois bundleflower populations in Oklahoma.…”
Section: Grazing Treatment Discussionmentioning
confidence: 99%